Daily and seasonal variation of traffic related aerosol pollution in Thessaloniki, Greece, during the financial crisis. (December 2015) - Vouitsis, Ilias; Amanatidis, Stavros; Ntziachristos, Leonidas; Kelessis, Apostolos; Petrakakis, Maximos; Stamos, Iraklis; Mitsakis, Evangelos; Samaras, Zissis
Abstract: Airborne urban particulate and gaseous pollutants measurements were conducted at the kerbside of a busy road and at a nearby urban background site of Thessaloniki, Greece, during a winter and a summer period. The main objective was to observe how the financial crisis has affected the air quality in the city, compared to previous measurements. Compared to a study conducted in 2006, the current work suggests that although average concentrations at the traffic affected site remain higher that in the urban background station, the differences are much smaller than in the past. A number of observations suggest a scenario of decrease in traffic activity and increase in biomass burning for residential heating. On this basis, the results suggest that traffic may be less important as an air quality contributor in a financially hit city. On the contrary, domestic heating appears as a significant contributor and affects areas of the city that were earlier not being of environmental concern. Because of the impact of biomass burning in residential areas, exposure calculations are required to estimate whether traffic or biomass burning is the overall highest contributors to daily PM dosages that citizens of the city are exposed to. Highlights: The importance of traffic on air quality has dropped in a financial crisis hit city. Biomass for domestic heating has significantly worsened the air in residential areas. Better control of biomass burning needed to alleviate air quality impacts.